Empowering youth through agricultural education: nurturing entrepreneurs and life skills at young age - Thumbarayan, Irene Jebamalar; Burhanuddin, Aimi Nasuha (Human Resources Management Academic Research Society (HRMARS), 2024)
Adding agriculture to preschoolers imparts essential life skills and underscores its significance in daily life. Beyond farming knowledge, it nurtures ethical and responsible business practices, which are vital in Malaysia's challenging job market for graduates. In an innovative educational project, school fields became dynamic spaces for preschoolers to explore vegetable cultivation. They gained hands-on experience, learning every aspect of farming, from nurturing plants to harvesting, consuming, and selling their produce. This initiative seamlessly integrated agriculture with entrepreneurship, aligning with Malaysia's goal of a competitive workforce and a robust economy. Recognising the educational importance of entrepreneurship, the Ministry of Education integrated entrepreneurial elements into the curriculum, enhancing this project's approach. In parallel, this project introduced young minds to entrepreneurship within an agricultural context. Preschoolers gained exposure and experience by seeking customers and selling their produce, a valuable lesson that extends beyond profit-making. The involvement of parents and the school community in purchasing the students' produce facilitated practical learning of sales techniques. From April to September 2022, 25 preschoolers collaborated in small groups, mastering planting, harvesting, bundling, and selling vegetables. The project's methodology, which integrated agriculture with entrepreneurship and actively involved parents and the school community, yielded significant positive outcomes in preparing preschoolers for future business ventures while fostering a sense of empowerment and responsibility towards society and the environment. The proceeds reinvested into the venture taught them resourcefulness and money-making strategies. This journey fostered teamwork, patience, and comprehension of real-world supply and demand dynamics, enriching their physical skills, self-esteem, and confidence, and preparing them for future business ventures. Empowering youth through agricultural and entrepreneurial education in their formative years lays a solid foundation for essential business skills and also develops values of social.